2021
DOI: 10.1002/joc.6994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atlantic multidecadal oscillation on interannual relationship between ENSO and East Asian early summer monsoon

Abstract: Impact of the Atlantic multidecadal oscillation (AMO) on the interannual relationship between the El Niño‐Southern Oscillation (ENSO) and East Asian early summer monsoon (EAESM) is investigated using observations and community atmosphere model (CAM) outputs. We find that the interannual ENSO–EAESM relationship displays a prominent decadal variation during 1951–2018, which is consistent with the AMO phase change, that is, a high ENSO–EAESM correlation appears during the negative AMO phase, while no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…We can find that the 2–4 and 8–10 year quasi‐periodic signals (IMF1 and IMF2) in the representative CPs have no correlation with PDO and AMO, but the 2–4 year oscillation in A1–A′1, B1–B′1, and A2–A′2 is positively related to the phase of ENSO (at 99% statistical significance level), for A5–A′5 is the opposite. Previous studies showed that the East Asia summer monsoon (EASM) is tends to stronger when is an El Niño event, and to shift the WPSH more northward; while La Niña is the opposite (Xu et al ., 2021). Because CP A5–A′5 is dominated by the relatively weak WPSH (Figure 2), it is natural to have a negative relationship with ENSO.…”
Section: Discussionmentioning
confidence: 99%
“…We can find that the 2–4 and 8–10 year quasi‐periodic signals (IMF1 and IMF2) in the representative CPs have no correlation with PDO and AMO, but the 2–4 year oscillation in A1–A′1, B1–B′1, and A2–A′2 is positively related to the phase of ENSO (at 99% statistical significance level), for A5–A′5 is the opposite. Previous studies showed that the East Asia summer monsoon (EASM) is tends to stronger when is an El Niño event, and to shift the WPSH more northward; while La Niña is the opposite (Xu et al ., 2021). Because CP A5–A′5 is dominated by the relatively weak WPSH (Figure 2), it is natural to have a negative relationship with ENSO.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the relationship between ENSO and the Asian climate can be modulated by Pacific, Atlantic and Indian Ocean signals, such as the Atlantic Multidecadal Oscillation (AMO), tropical Indian Ocean SST, and Pacific Multidecadal Oscillation (Chen et al., 2018; Xu et al., 2021; Yu et al., 2021). Xu et al.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Xu et al. (2021) pointed out that in the negative phase of the AMO, the ENSO‐East Asian early summer monsoon relationship is strong; however, in the positive phase, the relationship disappears. The relationship between the Indian summer monsoon rainfall and ENSO is intimately related to summer tropical Indian Ocean SST (Yu et al., 2021).…”
Section: Possible Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studying the multiscale periodic change in the early spring temperature is highly important for the prediction of the temporal evolution trend of plant growth and prevention of the formation of regional cli-mate disasters. Previous studies have indicated that multiscale climate signals, such as the El Niño/Southern Oscillation (ENSO), Pacific Interdecadal Oscillation, North Atlantic Multidecadal Oscillation, and North Atlantic Oscillation, are important factors of global and regional climates through ocean systems or atmospheric circulation (Knight et al 2006, Mann et al 2014, Xu et al 2021. Changes in the above global-scale climate signals can notably affect temperature variations in China and even the Northern hemisphere (Wyatt & Curry 2014, Jia et al 2017, Li et al 2015a).…”
Section: Introductionmentioning
confidence: 99%